Chiapa de los Indios and its «Antiquities» in the Light of the XIX Century - Lowe, Lynneth S. (2022)
Palabras claves: historia; arqueología; México; expedición científica; antigüedades; sitio arqueológico.   Abstract: This article aims to provide an overview of the first attempts of historical interpretation made during the XIX century to the pre-Hispanic settlement located in the outskirts of Chiapa de los Indios, the present city of Chiapa de Corzo, in Chiapas, pointing out the changes in its conception over time; such approaches were the result of the first scientific expeditions to the region, which combined the available archaeological evidence with historical, linguistic and anthropological data to infer the ethnicity of its inhabitants. The ancient settlement of Chiapa aroused the interest of travelers and explorers, such as the Abbe Brasseur de Bourbourg, Dr. Hermann Berendt or the archaeologist Eduard Seler, who associated it with the Chiapanec groups, famous for their military and expansionist reaches at the time of the Spanish Conquest. However, later archaeological research conducted since the mid-twentieth century identified its ascription as one of the main regional capitals of the Zoque culture in the Central Depression of Chiapas. The comparison between both approaches, that of nineteenth-century explorers and the other one provided by scientific archeology, makes it possible to highlight the wealth of the information recovered in terms of material, documentary and linguistic evidence, while illustrating the need for more profound comparative studies to achieve an ethnic assignation of archaeological sites.